The Holevich modification of the first dorsal metacarpal artery flap in coverage of thumb skin losses - Panagatla, Prakash; Kondapavuluri, Sindhuri; Ravula, Parvathi (International Journal of Research in Orthopaedics, 2019)
Background: Reconstruction of complex soft tissue defects of the thumb is a challenging problem. It is very important to reconstruct these defects using sensate flaps as the thumb pulp needs to be sensate for implementing the various functions of the thumb. The aim of this study is to report our experience on the safety and functional outcome of the innervated first dorsal metacarpal artery flap (FDMA) for soft tissue defects of thumb. Methods: During 18 month period, nine patients with a mean age of 29 years, male:female ratio of 8:1 underwent coverage of soft tissue defects of the thumb, of various volar and dorsal defects, using an innervated first dorsal metacarpal artery flap. Indications were postburn deformities and acute trauma. None of the patients had any neurorraphy. Outcome of the Holevich modification of FDMA flap was assessed with regards to survival and function, reachability for different locations of the thumb, recovery of sensation in terms of two-point discrimination (2PD), donor morbidity with regards to deformity and range of motion were analysed. Results: The mean size of the defect was 6.7 cm2. Average hospital stay was 5 days. Average time of sensory recovery was 6 months. The mean 2PD was 4 mm (range 2-6 mm). All patients had a normal active range of motion in the donor finger. One of nine patients had distal flap marginal necrosis of 3-4 mm; it healed with debridement and regular dressings over 12 days. Conclusions: The Holevich modification ensures the safety of the innervated FDMA flap in thumb defect coverage with good recovery of sensation.